Access to adolescent-responsive oral, mental, sexual, and reproductive healthcare services in Africa through dental clinics - Sam-Agudu, Nadia Adjoa; Osa-Afiana, Chinye; El Tantawi, Maha; Foláyan, Moréniké Oluwátóyìn (Frontiers in Oral Health, 2025)
In many healthcare systems, oral healthcare is provided separately from other clinical services. For 10–19-year-old adolescents in particular, this separation of care perpetuates the underutilization of oral health services and the neglect of oral health. Available evidence indicates that there are interconnections between oral, mental, sexual, and reproductive health (OMSRH) in adolescents. For African countries, there are opportunities to draw on lessons learned from HIV-centered models of integrated care to develop and evaluate dental clinic-centered models for integrating adolescent OMSRH services. This article makes a case for evidence-based adolescent OMSRH service integration in African countries. Integration is expected to align with the principles of sustainable development goals, universal healthcare, and the World Health Organization's calls for adolescent-responsive health services. We present a conceptual framework and propose an implementation science-guided blueprint for the integration of adolescent OMSRH care. The focus on dental clinics for integration can potentially increase access to, and use of oral healthcare while addressing adolescents’ mental, sexual and reproductive health needs. OMSRH integration for adolescents in African settings will require intensive engagement of adolescents and other crucial stakeholders. Further exploratory and implementation research is also needed to design and evaluate OMSRH integration models to establish best practices for long-term impact on adolescent health outcomes.